2011
DOI: 10.1182/blood-2010-12-323113
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1–expressing stromal cells constitute a specific niche for pre-BII cell development in mouse bone marrow

Abstract: In the bone marrow (BM), stromal cells constitute a supportive tissue indispensable for the generation of pro-B/pre-BI, pre-BII, and immature B lymphocytes. IL-7-producing stromal cells constitute a cellular niche for pro-B/pre-BI cells, but no specific stromal cell microenvironment was identified for pre-BII cells expressing a functional pre-B cell receptor (pre-BCR). However expression of the pre-BCR represents a crucial checkpoint during B-cell development. We recently demonstrated that the stromal cell der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
5
66
1
Order By: Relevance
“…Indeed, it has been shown that pre-BII cells are not able to contact stromal cells that are not secreting GAL1 (ref. 21). The significant LacNAc content of pre-BII cells is therefore an important determinant for cell recognition and cell niche specificity.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been shown that pre-BII cells are not able to contact stromal cells that are not secreting GAL1 (ref. 21). The significant LacNAc content of pre-BII cells is therefore an important determinant for cell recognition and cell niche specificity.…”
Section: Articlementioning
confidence: 99%
“…Expression of the pre-B cell receptor (pre-BCR) represents a crucial checkpoint during B-cell development as this receptor controls pre-BII cell development and the selection of the Igm repertoire 23 . We have found that pre-BII cells are associated to medullar stromal cells secreting GAL1 that constitute a specific pre-BII cell niche in the bone marrow 21 . At the contact zone between pre-BII and stromal cells, GAL1, preBCRs and glycosylated integrins relocalize 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as previously described. 7,19,30 Briefly, 20-mm-thick sections were transferred to adhesive-coated slides with the CryoJane Tape-Transfer system according to the manufacturer's protocol (Instrumedics). Bone sections (after fixation in methanol) were incubated for 1 hour at room temperature with a blocking solution (PBS, 2% BSA, 1% donkey serum, 1% FCS).…”
Section: Histology and Imagingmentioning
confidence: 99%
“…Galectin-1 has been found to be differentially expressed in various normal and pathological tissues and to mediate a series of signal pathways involving cellular adhesion, migration, proliferation, differentiation, and death (3)(4)(5)(6). For example, the mesenchymal stem cells of the bone marrow highly express galectin-1 protein (7,8), and galectin-1-expressing stromal cells constitute a specific niche for pre-BII cell development in mice (9). Upon erythroid differentiation of leukemic K562 cells, the galectin-1 is externalized and bound to the cell surface (10).…”
mentioning
confidence: 99%